Problems of learning and teaching modern Arabic/ Musykilah Ta’lîmi al-Lugha al-Arabiyah al-Hadîtsah wa Ta’lîmiha - Firdaus, Dadang (Al-Manar, 2022)
AbstractTeaching Arabic is a form of classical teaching that is still ongoing from generation to generation to this day. In addition , the learning process applied is of course very varied . The curriculum provided, the methods applied and the approaches and techniques implemented have undergone many changes. Thus, of course, it is hoped that an escalation in its application along with the times and the increasing need for the use of modern facilities, this is in line with the rapid rate of utilization of media or learning facilities in all branches of science. Therefore, it is hoped that learning Arabic certainly does not lose its involvement in modern learning models. The use of technology-based learning media today is highly encouraged in Arabic learning, the use of media in an approach turns out to have a very large influence in stimulating the interest and attention of students, while the media in question includes various forms, including internet-based learning media, television-based learning media, audio-based learning media and others, so that learners no longer feel Arabic as "old school" material, but rather a uniquely interesting and modern material.ملخّصإنّ تعليم والتعلم اللغة العربية عملية فعلها فعلها المدرس والطلاب، والتعليم عملية نقل المعلومات اللغوية من المدرس إلى طلابه. أمّا التعلم فهو سعي فعله الطالب لنيل الفهم والمعلومات اللغوية حتى يقدر أن يرقي نموّ كفائته اللغوية الأربعة. ولكنّ الواقع إنّ كثيرا من هٰذي العملية لم يصل إلى الغاية، لا تؤدي إلى تمام التعليم ونجاح التعلم ولم يصل إلى أخداف مقصودة. وكانت لهذا الفشل مشكلة أساسية ‎التي قامت على المعلم والمتعلم وما بينهما من أمور مدافعة لهذا المجال وهي تفصيل المشكلة إلى خمسة أنواع، وهي : مشكلة المعم ويسمى هذه المشكلة بمشكلة التعليم، ومن المشكلات التي ملكها المعكلم هي عدم إتقان المعلم لمادته ونقصان كفاءة استيعاب الطرق، ونقصان كفاءة استيعاب المادة،ونقصان كفاءة استيلاء احوال الطلاب، والمشكلات كانت على الطلاب منها الطلاب، ومشكلات التي شعرها الطلاب ويسمى بمشكلة التعلم بعض الأنماط وظروف المشاغبين ومنها نقصان الرغبة التي تؤثر إلى عدم الاهتمام عن إلى الدرس، نقصان المعرفة ما يلزم عليهم استيعابها قبل أن ينال معلومات جديدة من المادة اللغوية والمشكلات المنهجية التي تتعلق بقانون الحكومية والمدرسة عن حصة الدرس اللغة العربية ومادتها، ومشكلة وسائل التعليم التي تؤثر إلى المشكلة الأولى الثانية في تنفيذ التعليم وتأدية التعلم ومشكلة البيئة .